2017
DOI: 10.1038/bmt.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic cell transplantation in patients with AML not achieving remission: potentially curative therapy

Abstract: Patients with acute myeloid leukemia (AML) who fail to achieve complete remission (CR) have a dismal prognosis. Although data suggest that durable remissions can be achieved in approximately 30% of patients with refractory or relapsed AML after allogeneic hematopoietic cell transplantation (HCT), only a small fraction of those patients are offered this therapeutic option. Importantly, patients with primary refractory AML have distinctly better outcomes following allogeneic HCT than those with refractory relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Several studies have shown that APMF is associated with poor response to chemotherapy, and median survival time is usually less than 1 year [2][3][4][5]. Because allogeneic HCTs have curative potential for relapsed, refractory, and poor prognostic myeloid malignancies [19], HCT has been attempted to treat APMF. Although a limited number of APMF cases treated with HCT have been reported [8][9][10][11][12], the outcome of HCT in patients with APMF has never been systematically studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that APMF is associated with poor response to chemotherapy, and median survival time is usually less than 1 year [2][3][4][5]. Because allogeneic HCTs have curative potential for relapsed, refractory, and poor prognostic myeloid malignancies [19], HCT has been attempted to treat APMF. Although a limited number of APMF cases treated with HCT have been reported [8][9][10][11][12], the outcome of HCT in patients with APMF has never been systematically studied.…”
Section: Discussionmentioning
confidence: 99%
“…Pursuing stem cell transplantation depends on the fitness and age of the patient, risk of relapse after having achieved a CR, availability of a donor, access to a transplant center, and financial eligibility. Patients with higher risk features such as poor‐risk cytogenetics or adverse mutations, patients with therapy‐related AML, patients who fail to obtain a CR after induction (primary induction failure), or patients with relapsed refractory disease may be appropriate candidates for transplantation . The use of alternative stem cell sources (haploidentical donors, umbilical cord blood, and matched unrelated donors) and reduced intensity and nonmyeloablative conditioning regimens have expanded the eligibility for transplantation .…”
Section: Treatment Of Acute Myeloid Leukemiamentioning
confidence: 99%
“…15 The use of alternative stem cell sources (haploidentical donors, umbilical cord blood, and matched unrelated donors) and reduced intensity and nonmyeloablative conditioning regimens have expanded the eligibility for transplantation. 15 A donor search should be initiated in patients with any nonfavorable risk while the patient is undergoing induction chemotherapy. 8 Although no standard maintenance treatment exists, maintenance may be used after postremission chemotherapy or posttransplantation in certain patients who are at a high risk of relapse (such as those who are FLT3-positive and/or who have detectable residual disease after transplantation), and may consist of tyrosine kinase inhibitors (TKIs), hypomethylating agents, and/or prophylactic donor lymphocyte infusions (in posttransplantation patients only).…”
Section: Standard Aml Treatmentmentioning
confidence: 99%
“…Allogeneic hematopoietic cell transplantation (HCT) is the only potential curative therapy for patients with nonremission myeloid malignancies [1][2][3]. Cord blood transplantation (CBT) is an acceptable alternative donor source for patients without HLA-matched related or unrelated donors in need of allogeneic HCT [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%